Neurological outcome at 30-day as an estimator of 1-year functional status after out-of-hospital cardiac arrest with post-encephalopathy. (14th October 2021) - Nitta, G; Matsuda, J; Kato, S; Hada, Y; Inaba, O; Matsumura, Y; Nozato, T; Ashikaga, T; Sasano, T
Abstract: Background: Implantation of implantable cardioverter-defibrillators (ICD) for secondary prevention is fully recommended for those with an estimated survival over 1-year with a good functional status. However, we often face the difficulty to estimate the functional status and hesitate to implant ICD for patients with post-resuscitation encephalopathy. Methods: There were 2391 out-of-hospital cardiac arrest (OHCA) patients transferred to 2 hospitals. We included 405 cardiovascular arrest patients, who got return of spontaneous circulation (ROSC) from January 2015 to December 2018. Among the patients, 343 patients could be considered to be implanted ICD for secondary prevention according to the initial waveform or the causes of OHCA. At 1-month later, 184 patients (54%) survived. To assess the association of functional status at 30-day and 1-year, we investigated patients' characteristics, pre-hospital information and clinical findings, and evaluated the neurological outcome according to the cerebral performance category (CPC) scale. Results: At 1-month later, 145 patients (79%) survived with CPC≤2, and 39 patients (21%) survived with CPC>2. Bystander CPR (P=0.009), pre-hospital ROSC (P<0.001), low lactate level on admission (P=0.001), high geriatric nutritional risk index score (P<0.001) and without ECMO (P=0.002) were significantly associated with good neurological outcome at 30-day. The 1-year Kaplan-Meier event rate revealed significantly different survival rate (CPC>2 at 30-day:38.5%, vs CPC≤2 at 30-day:97.2%; P<0.001). In multivariate analysis, CPC scale at 30-day (OR 0.022; 95% CI 0.003–0.140; p<0.001) was the independent predictor of favorable neurological outcome at 1-year. Among the patients with CPC>2 at 30-day, only 3 patients (7.7%) of CPC=3 achieved the improvement of neurological outcome at 1-year (CPC≤2), while no patient of CPC=4 did. And one patient (2.5%) with CPC=3 was implanted ICD during the follow-up period. Twenty-five patients (64%) died of non-cardiovascular death with frailty of post-resuscitation encephalopathy after they were transferred to other hospital with the acceptation and intention of the do-not-attempt-resuscitation. Conclusions: Neurological prognosis at 30-day after OHCA might be an estimator of 1-year functional status to guide us to implant ICD for secondary prevention. FUNDunding Acknowledgement: Type of funding sources: None.